Microscopic Hair Shaft Analysis in Iraqi Population - Taghreed K.S Al-Ashoer (Journal of Global Pharma Technology, 2016)
Hair is a biological evidence contributing important role at a crime scene. Microscopic hair analysis can help to identify of a suspect in forensic investigation. The principle of this study was to find diagnostic aspects of the hair shaft from the Arab Iraqi population through compound light and scanning electron microscopy examination and analysis of the shaft diameter, medullary index, ovoid body and medulla type for human scalp hair shaft in forensic analysis in the crime scene investigation. The investigation under compound light microscope included 76 out of 100 samples because of 24 hairs samples were deep black view and photos showed no data. The shaft diameter range of hair samples was 34.75 to 115µm.The medulla type classified into four groups as absent type (78%), continuous (13 %), fragment (8%) and interrupted type (1%). The medullary index of human hair was observed in ranging from 0.083- 0.189. The ovoid bodies in hair shaft samples were absent (80%) and present (20%) of all samples. In this study reported that no significant differences in shaft diameter, medullary index, medulla type and ovoid body among male and female groups. The scanning electron microscope results indicated that high amount of hair shaft damage and the difference between the individuals in outer cuticle scale pattern showed that all samples were imbricate type, while chipped, lifting, jagged and smooth reported 17%, 8%, 4%and 1%, respectively.Keywords: Hair shaft, Microscopic analysis, SEM, Iraq.